The Spheroid Light Microscopy Image Atlas for morphometrical analysis of three-dimensional cell cultures - Eva Blondeel; Arne Peirsman; Stephanie Vermeulen; Filippo Piccinini; Felix De Vuyst; Diogo Estêvão; Sayida Al-Jamei; Martina Bedeschi; Gastone Castellani; Tânia Cruz; Sándor Dedeyne; Maria José Oliveira; et al. (Scientific Data)
Abstract The application of three-dimensional (3D) cell cultures such as spheroids and organoids is growing in popularity both in academia and industry. However, morphology of the 3D architecture remains remarkably understudied. Here, we introduce an open-access Spheroid Light Microscopy Image Atlas (SLiMIA) that can serve as a training set for morphology studies of 3D cell cultures. We provide images with a variety of metadata: 9 microscopes, 47 cell lines, 8 culture media, 4 spheroid formation methods and multiple cell seeding densities; totalling approximately 8,000 images of spheroids. This comprehensive dataset can guide spheroid researchers and promote economizing of resources by advancing 3D cell culture optimization, standardization and implementation by the community at large. Considering the exponentially growing interest in spheroid morphometrical analyses and the emerging technological possibilities to do so, this atlas can be applied to train and develop image segmentation models to deepen our understanding of 3D spheroid morphometry in biomedical research.